A MOF-based carrier for in situ dopamine delivery. Issue 45 (18th July 2018) - Pinna, Alessandra; Ricco', Raffaele; Migheli, Rossana; Rocchitta, Gaia; Serra, Pier Andrea; Falcaro, Paolo; Malfatti, Luca; Innocenzi, Plinio
Abstract : Pinna and co-workers report the design of a MOF-based magnetic composite for long-term release of dopamine in the PC12 cell line. Abstract : MIL-88A (Fe) MOF crystals were nucleated and grown around a polymer core containing superparamagnetic nanoparticles to assemble a new class of biocompatible particles for magnetophoretic drug delivery of dopamine. The carrier enabled efficient targeted release, dopamine protection from oxidative damage, long-term delivery and improved drug delivery cost-efficiency. After loading, dopamine was stable within the carrier and did not undergo oxidation. Drug release monitoring via spectrofluorimetry revealed a shorter burst effect and higher release efficiency than silica based carriers. The in vitro cytotoxicity at different MOF concentrations and sizes was assessed using PC12 cells as the neuronal cell model. The drug was directly uptaken into the PC12 cells avoiding possible side effects due to oxidation occurring in the extracellular environment.